2013
DOI: 10.1890/es13-00257.1
|View full text |Cite
|
Sign up to set email alerts
|

Marine reserve networks conserve biodiversity by stabilizing communities and maintaining food web structure

Abstract: Citation: Wing, S. R., and L. Jack. 2013. Marine reserve networks conserve biodiversity by stabilizing communities and maintaining food web structure. Ecosphere 4(11):135. http://dx.doi.org/10.1890/ES13-00257.1Abstract. Theory predicts that networks of fully protected marine reserves conserve biodiversity by stabilizing communities and maintaining food web structure in the face of inadequately constrained fishery exploitation. To test these ideas we examine trends in species incidence, community and trophic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…For example, C. lepidoptera (butterfly perch), a common prey species of large fish, were less likely to be present in reserves in both regions and were less abundant when present in reserves in the Marlborough Sounds. Decreased density of C. lepidoptera was likely associated with increased predation pressure by large fishes inside reserves (Wing and Jack ). In addition to altering predation pressure, it was possible that fishing may have affected interspecific competition for food and space within the reef fish community (Denny et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, C. lepidoptera (butterfly perch), a common prey species of large fish, were less likely to be present in reserves in both regions and were less abundant when present in reserves in the Marlborough Sounds. Decreased density of C. lepidoptera was likely associated with increased predation pressure by large fishes inside reserves (Wing and Jack ). In addition to altering predation pressure, it was possible that fishing may have affected interspecific competition for food and space within the reef fish community (Denny et al.…”
Section: Discussionmentioning
confidence: 99%
“…The inner waters of Fiordland were closed to commercial fishing as a part of the Fiordland Marine Management Act—2005, and further recreational restrictions were put in place for catch of red rock lobsters ( J. edwardsii ) and blue cod ( P. colias ) in the inner fjords (Ministry of Primary Industries ). Here, we group sites as fished or reserve based on whether they are located within a no‐take marine reserve or elsewhere, as fishing effects were still observed between commercial exclusion zones and no‐take marine reserves (Wing and Jack ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One reason for weaker and mixed outcomes in diversity is that not all species increase-and some decline-after reserve establishment (Micheli et al 2004b). As detailed in this section, community-level responses Variability in species diversity Decrease S: (Bates et al 2014) Variability/turnover in community assemblage/structure Lower S: (Fraschetti et al 2013, Mellin et al 2014, Wing & Jack 2013 Occurrence of nuisance species outbreaks Lower S: (McCook et al 2010) Resistance to disturbance Inconsistent or unaffected M: (Selig et al 2012, Worm et al 2006 Recovery rate Inconsistent or lower M: (Graham et al 2011, Worm et al 2006 Invasiveness Unaffected M: (Burfeind et al 2013, Guidetti et al 2014 a Increase can refer to a greater value (and decrease a smaller value) inside compared with outside reserves (more common) or after compared with before reserve establishment, depending on the study. b S, single study; M, meta-analysis, in which the response indicated is the cross-study average response, which might vary among studies.…”
Section: Community Consequences Of Marine Reservesmentioning
confidence: 99%
“…Further, differences in the complexity and connectivity of food webs can be directly linked to community dynamics and resilience under stress (e.g. Wing & Jack, ). As a corollary, understanding the sources and fate of organic matter within coastal food webs is a vital step towards understanding both ecosystem function and variability in fisheries production within coastal systems (Friedland et al, ; Ware & Thomson, ).…”
Section: Introductionmentioning
confidence: 99%